Infection Control In Orthodontics. - Vyas, Hariyali; Shukla, Chandresh; Shrivastava, Trilok; Ali, Syed Akbar; Dixit, Siddharth; Patel, Aakash (Journal of Neonatal Surgery, 2025)
Infection control is a critical component of orthodontic practice to ensure the safety of both patients and healthcare professionals. The orthodontic environment presents unique challenges due to frequent patient contact, use of reusable instruments, and exposure to saliva and blood. This article reviews current principles and protocols of infection prevention in orthodontics, including standard precautions, sterilization and disinfection methods, instrument processing, and operatory asepsis. Emphasis is placed on the role of personal protective equipment (PPE), hand hygiene, and surface barrier techniques in minimizing the risk of cross-contamination. Advances in materials and technologies, such as single-use devices and improved sterilization systems, are also discussed. Additionally, the article highlights the importance of adherence to guidelines provided by organizations like the CDC and WHO. Effective implementation of infection control measures not only reduces the risk of disease transmission but also enhances the quality of care and patient confidence in orthodontic treatment..